2016
DOI: 10.1007/s00423-016-1520-2
|View full text |Cite
|
Sign up to set email alerts
|

“Silent” kidney stones in “asymptomatic” primary hyperparathyroidism—a comparison of multidetector computed tomography and ultrasound

Abstract: PurposeThe purpose of this study was to demonstrate the high number of kidney stones in primary hyperparathyroidism (PHPT) and the low number of in fact “asymptomatic” patients.MethodsForty patients with PHPT (28 female, 12 male; median age 58 (range 33–80) years; interquartile range 17 years [51–68]) without known symptoms of kidney stones prospectively underwent multidetector computed tomography (MDCT) and ultrasound (US) examinations of the urinary tract prior to parathyroid surgery. Images were evaluated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
4
1
2
Order By: Relevance
“…16,17 The best method for diagnosing renal tract stones remains debatable but CT scans appear to be more sensitive as evident from our and other studies. 18,19 In our series, biochemical parameters did not differ significantly between 'stone formers' and 'nonstone formers' although other authors have demonstrated a higher risk of stone formation in patients with high urinary calcium levels. 15,20 Cassibba and colleagues, 21 showed that in patients with PHPT, overt nephrolithiasis is associated with higher levels of serum calcium and PTH confirming the role of PHPT as a risk factor with further suggestions that silent nephrolithiasis helps to identify a more active and severe form of disease and these patients meet surgical indication more frequently than PHPT without stone disease.…”
contrasting
confidence: 56%
“…16,17 The best method for diagnosing renal tract stones remains debatable but CT scans appear to be more sensitive as evident from our and other studies. 18,19 In our series, biochemical parameters did not differ significantly between 'stone formers' and 'nonstone formers' although other authors have demonstrated a higher risk of stone formation in patients with high urinary calcium levels. 15,20 Cassibba and colleagues, 21 showed that in patients with PHPT, overt nephrolithiasis is associated with higher levels of serum calcium and PTH confirming the role of PHPT as a risk factor with further suggestions that silent nephrolithiasis helps to identify a more active and severe form of disease and these patients meet surgical indication more frequently than PHPT without stone disease.…”
contrasting
confidence: 56%
“…Several recent studies suggest that the prevalence of occult urolithiasis ranges from 7–36% as assessed by ultrasound. 11,12,30,45,46 Rates may be higher when CT is used because ultrasound can miss small stones. 46 Most of our patients had renal ultrasound rather than abdominal CT.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,30,45,46 Rates may be higher when CT is used because ultrasound can miss small stones. 46 Most of our patients had renal ultrasound rather than abdominal CT. The higher prevalence of stones in the group screened with CT suggests that the prevalence of occult renal stones could be underestimated by this study.…”
Section: Discussionmentioning
confidence: 99%
“…Die klassische Symptomtrias "Stein-, Bein-und Magenpein" in Anspielung auf vermehrte Nierensteinbildung, erhöhte Knochendemineralisierung und Entzündungen der Magenschleimhaut ist seltener geworden. Bei genaueren klinischen Untersuchungen konnten allerdings gehäuft Nierensteine und beeinträchtigte Muskelfunktionen beobachtet werden [3,4].…”
Section: Primärer Hyperparathyreoidismusunclassified